Evaluación de la remolacha forrajera (beta vulgaris, l.) al 5%, 10%, 15% en la alimentación de cuyes hembras en etapa de empadre hasta destete en el barrio Lasso Centro - Anchatuña Maigua, Betty Elizabeth (2016)
This research was conducted in Lasso Center. The overall objective of the research was: "To evaluate the use of fodder beet (vulgaris vein, l.) 5%, 10%, 15% in female guinea pigs feeding on breeding until weaning stage, determining their influence on reproductive variables such as maternal weight, weight of kits, conception rate, number of offspring, mortality, morbidity and cost-effective. Assess weight gain in rabbits until weaning. Establish ing the costs of reproduction. For this research design was applied completely random, on 40 female guinea pigs three months old established four groups of 10 animals, these were placed in the pools set according to each treatment and were selected: Witness fodder, T1 fodder plus 5% of fodder beet, fodder T2 plus 10% of fodder beet, fodder T3 plus 15% of fodder beet. In the following research results were obtained with greater weight gain T3 reaching a final weight of 1272, followed by 3 g T2 with an average weight of 1192.6, as to the kits born the best result was T1 an average weight of 145 g at weaning was the most projection T2 with an average weight of 405 g....